Employment Law Industrial Revolution Perspective 4.0 - Satria Pardede (International Asia Of Law and Money Laundering (IAML), 2022)
This article aims to find solutions due to educated unemployment in the era of the Industrial Revolution 4.0. The problem of the high level of labor with the availability of inadequate job vacancies further adds to the problems in the employment sector. Data from the Central Statistics Agency shows that the unemployment rate is quite high at the high school and university level compared to the diploma level. On the other hand, employers consider that they find it difficult to find potential workers who fit the desired criteria. With the regulation on the use of foreign labor is one of the things that can help in overcoming the needs of Labor. However, the existence of regulations on foreign labor must be examined further. Don't let the existence of these regulations actually close the opportunity for Indonesian workers to get a job in Indonesia. It is necessary to find a solution to solve the problem in the field of employment. Any party can help reduce the unemployment rate in the era of the Industrial Revolution 4.0. The government has a central role in reducing educated unemployment. The government can evaluate employment legislation to protect the workforce and respond to the Industrial Revolution era 4.0. In addition, the government can review the curriculum at every level of education so that graduates have the soft skills and hard skills needed in the era of the Industrial Revolution 4.0. Each educational unit has a special focus in preparing its graduates in the era of the Industrial Revolution by adding practical learning hours. In addition, graduates must have innovative thinking in creating new jobs in the era of the Industrial Revolution 4.0.